Fishes from the Upper Jurassic of Torres Vedras, Portugal - Costa, Bruno Leite Pereira (2022)
In this study, fossil hybodontiform and neopterygian specimens from the Upper Jurassic of Torres Vedras are reported. Material was collected on the surface of the marine deposits at the top of Praia Azul Member, Lourinhã Formation, dating between upper Kimmeridgian-lower Tithonian; and on the surface of the transitional deposits of Cambelas fossil site, Freixial Formation, dating between middle-upper Tithonian, Upper Jurassic. Fossils are housed in the CI2Paleo of Sociedade de História Natural, in Torres Vedras. Hybodontiforms are represented by 30 isolated teeth, which are attributed to Hybodus cf. reticulatus, as per diagnostic evidences on the main cusp, cutting-edges, and, especially, the root. Neopterygians are represented by 29 isolated or partially associated body scale specimens, diagnosed as cf. Ginglymodi; and 64 isolated and partially articulated prearticular and vomerine teeth referred to Pycnodontiformes indet. This work hopefully improves our understanding about the fish diversity and occurrences of the Upper Jurassic of Portugal; Resumo: Neste estudo são reportados exemplares fósseis de hybodontiformes e neopterígios do Jurássico Superior de Torres Vedras. Este material foi recolhido à superfície dos depósitos marinhos no topo do Membro da Praia Azul, Formação da Lourinhã, datando o Kimmeridgiano superior-Tithoniano inferior; e à superfície dos depósitos transicionais da jazida fóssil de Cambelas, Formação do Freixial, datando o Tithoniano médio-superior, Jurássico Superior. Os fósseis estão alojados no CI2Paleo da Sociedade de História Natural, em Torres Vedras. Os hybodontiformes são representados por 30 dentes isolados, atribuídos a Hybodus cf. reticulatus, conforme evidências diagnósticas na cúspide principal, bordo cortante e, especialmente, a raiz. Os neopterígios são representados por 29 espécimes de escamas corporais isoladas ou parcialmente associadas, diagnosticadas como cf. Ginglymodi; e 64 dentes pré-articulares e vomerinos isolados e parcialmente articulados, atribuídos a Pycnodontiformes indet. Esperançosamente, este trabalho aprimora a nossa compreensão acerca da diversidade e ocorrências dos peixes do Jurássico Superior de Portugal.